Tantangan dan Strategi Implementasi Mata Pelajaran PPKn di Era Digital - Rahmi Gustifal; Windy Wulan Septina; Adrias Adrias; Nur Azmi Alwi (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This study evaluates the challenges and strategies for implementing the subject of Pancasila and Civic Education (PPKn) in the digital era using a literature review method. The research findings identify several main obstacles, such as limited internet access, lack of digital devices, low digital skills among teachers and students, insufficient technical support, and a scarcity of quality digital resources. To address these challenges, several strategies are proposed, including the development of technological infrastructure, digital skills training for teachers and students, and the provision of engaging and interactive digital learning resources. With the implementation of these strategies, it is expected that PPKn education will become more effective and enhance student motivation and engagement. These findings have significant implications for the development of educational policies and teaching practices of PPKn in Indonesia in facing the challenges of the digital era.